Test Equating by Common Items and Common Subjects: Concepts and Applications - Chong Ho Yu; Sharon E. Osborn-Popp (Practical Assessment, Research, and Evaluation, 2005)
Accessed 34,044 times on https://pareonline.net from May 15, 2005 to December 31, 2019. For downloads from January 1, 2020 forward, please click on the PlumX Metrics link to the right.
Keywords: Equating